Corrosion of low-carbon steel in sodium chloride solution containing a water-soluble fraction of humic acid - Doskočil, Leoš; Horák, Tomáš; Honč, Jiří (Tanger, 2022)
Humic acids are a heterogeneous mixture of organic compounds that are naturally found in water and soil. In recent years, there has been a growing interest in the application of green fertilizers containing humic acids in agricultural activities. Water-soluble fraction of humic acid (WSHA) can be released from these fertilizers and subsequently interact with metallic materials (e.g. steel) located in soils and waters. WSHA were leached from an aqueous suspension of humic acids isolated from South Moravian lignite. Corrosion tests were performed on a low-carbon steel using a potentiodynamic polarization test and electrochemical impedance spectrometry. Results suggest that corrosion was initially promoted due to the formation of complex compounds of water-soluble humic acids with released iron ions. After a long time, a positive effect of WSHA was observed as the corrosion resistance of low-carbon steel increased.

Humic acids are a heterogeneous mixture of organic compounds that are naturally found in water and soil. In recent years, there has been a growing interest in the application of green fertilizers containing humic acids in agricultural activities. Water-soluble fraction of humic acid (WSHA) can be released from these fertilizers and subsequently interact with metallic materials (e.g. steel) located in soils and waters. WSHA were leached from an aqueous suspension of humic acids isolated from South Moravian lignite. Corrosion tests were performed on a low-carbon steel using a potentiodynamic polarization test and electrochemical impedance spectrometry. Results suggest that corrosion was initially promoted due to the formation of complex compounds of water-soluble humic acids with released iron ions. After a long time, a positive effect of WSHA was observed as the corrosion resistance of low-carbon steel increased.
Corrosion of low-carbon steel in sodium chloride solution containing a water-soluble fraction of humic acid
Keywords: corrosion; low-carbon steel; humic acid; corrosion; low-carbon steel; humic acid